Cropping patterns for phenology stability and resource conservation under extreme climates - Ahmad, Aqeel; Shahzadi, Iqra; Ali, Qurban; Umer, Muhammad; Yasin, Nasim Ahmad; Akram, Waheed; Wu, Tingquan; Khan, Waheed Ullah; Shah, Anis Ali (Frontiers in Agronomy, 2025)
ContextCultivation pattern is the foundation of agricultural policy, enabling farmers to perform various farming operations efficiently. In the meantime, with an increasing frequency of extreme climate events, it is imperative to devise low-cost strategies to anticipate disastrous climate events and achieve regional food security even in regions facing typhoons, floods, and extreme temperatures.ObjectiveThe study was primarily conducted to evaluate crop cultivation patterns, focusing on their intrinsic climate mitigation potential and phenological stability to secure sufficient food.MethodsOverall, the study was performed in three phases: i) crop type evaluation, ii) cultivation pattern analysis, and iii) cropping area analysis. In the first phase, the study used climate data of 1979–2020 with reference to seven crop types (i.e., cereals, oilseed, vegetables, beans, peas, nuts, and tubers) and evaluated yield reductions and phenological shifts.Results and conclusions: The results showed that tubers and nuts were the most resilient crops to extreme environmental events, whereas cereals (conventional staple crops) and oilseed (essential food crops) were most vulnerable to extreme climate events. Time-course phenological stability was higher in nuts and tubers, which possessed elevated resistance against phenological shifts. In the second phase, intercropping was highlighted as a better cultivation pattern; however, the recommended cultivation pattern was agroforestry due to its significant advantages over alley cropping, forest farming, and windbreaks. The third phase recommended incorporating windbreak plants in the perpendicular single-row formation with an interrow distance of 20 r (r—horizontal radius of the tree canopy).SignificanceOverall, the study aligns the fundamental aspects of agroecology with redesigning crop cultivation policies and has global implications in agricultural systems to mitigate extreme environments and ensure food security.